Islamic Ethics as the Foundation for Science and Technology Education in Elementary Schools: A Case Study at SDN Paduran Sebangau 2 - Muhamad Abdul Anam; Hamdanah Hamdanah; Normuslim Normuslim (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to analyze how Islamic ethics are operationalized as the foundation of science and technology education at SDN Paduran Sebangau 2. This study employs a qualitative approach using an intrinsic case study design through in-depth interviews, participatory observation, and analysis of learning documents. Informants included the school principal, classroom teachers, Islamic education teachers, and upper-grade students. Data analysis was conducted thematically using source and method triangulation to ensure the credibility of the findings. The results indicate that Islamic ethics are systematically integrated from the lesson planning stage, actualized in STEM pedagogical practices, internalized into students’ digital ethical awareness, transmitted through teachers’ exemplary behavior, and reinforced by the school culture. Values such as trustworthiness, honesty, responsibility, and the common good are translated into concrete pedagogical indicators in the use of technology in the classroom. These findings affirm a shift from a value-neutral STEM learning paradigm toward value-driven learning, where science and technology are understood as tools for character development. This study contributes theoretically to the integration of Islamic ethics, character education, and digital citizenship, and practically demonstrates an implementable model of value-based STEM education in elementary schools.